Effect of once‐daily tadalafil on confidence and perceived difficulty in performing sexual intercourse in men who were incomplete responders to as‐needed PDE5 inhibitor treatment. Issue 7 (25th March 2014) - Seftel, A. D.; Rosen, R. C.; Hayes, R. P.; Althof, S.; Goldfisher, E.; Shen, W.; Sontag, A.
Summary Introduction For men with erectile dysfunction (ED), the expectation of difficulty and level of confidence in achieving and maintaining an erection have an impact on sexual performance. Objective and methods This 12‐week, double‐blind study investigated once‐daily tadalafil (2.5 mg titrated to 5 mg or 5 mg) (n = 176) or placebo (n = 79) on confidence and perceived difficulty in performing sexual intercourse in men with ED who were incomplete responders to as‐needed phosphodiesterase‐5 inhibitor therapy. The Confidence in Performing Sexual Intercourse Questionnaire (CPSIQ) and Difficulty in Performing Sexual Intercourse Questionnaire (DPSIQ) were administered at baseline and 12 weeks. Results The mean change in CPSIQ for the tadalafil group was 1.8, which represents a shift from 'very low' to 'moderate' sexual confidence vs. a mean change of 0.5 in the placebo group (p < 0.0001). The mean change in DPSIQ for tadalafil was 1.6, which represents a shift from 'very difficult' to 'moderately' or 'slightly difficult' sexual performance vs. a mean change of 0.4 in the placebo group (p < 0.0001). Among men receiving tadalafil with an International Index of Erectile Function–Erectile Function (IIEF–EF) end‐point score of ≥ 26 or who achieved a minimal clinically important difference in IIEF–EF score at end‐point, the mean changes in CPSIQ were 3.0 and 2.4, respectively (both p < 0.0001). Conclusion Once‐daily tadalafil vs. placebo improves confidence and decreases difficulty in performing sexual intercourse for men with ED who were incomplete responders to as‐needed PDE5 inhibitor therapy.